The new (ethno)musicologies - Stobart, Henry, 1958- (Europea ;, 2008)
This collection of essays addresses and critically examines key issues in contemporary ethnomusicology. Set in two parts, the volume explores ethnomusicology's shifting disciplinary relationships and plots a range of potential developments for its future.